2022
DOI: 10.1111/ejss.13281
|View full text |Cite
|
Sign up to set email alerts
|

Water‐based spent drilling mud regulates hydrophysical properties of coarse‐textured loessial soil

Abstract: Amendment application is one of the effective measures used to remediate structural problems in coarse‐textured soils. However, the application of water‐based spent drilling mud (WBSM) as a potential amendment and its associated impacts on physical and hydraulic soil properties is not well‐studied. This research aimed to investigate the effect of the application of WBSM on basic hydrophysical properties of coarse‐textured loessial soil sampled from the Loess Plateau, China. Application of WBSM to repacked loes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 108 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…In addition, delayed N fertilization clearly attenuated the magnitude of N 2 O emissions after straw additions, whereby soil pH was the dominant regulator for N 2 O emissions under different straw returning forms and N application. The study by Fu et al (2022) showed that amendment application of water‐based spent drilling mud (WBSM), a candidate measure used to remediate structural problems in coarse‐textured soils, reduced the percentage of soil pore sizes >30 μm, but increased the proportion of medium pore sizes (≥30–50 μm), micro pore sizes (≥0.3–5 μm), and extremely micro pore sizes (<0.3 μm), owning to the clogging effect of the fine and clay particles contained in WBSM. In addition, WBSM application increased soil available water‐holding capacity and reduced evaporative water loss, which has useful implications for the management of coarse‐textured soils with a distinct water deficit in fragile ecosystems.…”
Section: Figurementioning
confidence: 99%
“…In addition, delayed N fertilization clearly attenuated the magnitude of N 2 O emissions after straw additions, whereby soil pH was the dominant regulator for N 2 O emissions under different straw returning forms and N application. The study by Fu et al (2022) showed that amendment application of water‐based spent drilling mud (WBSM), a candidate measure used to remediate structural problems in coarse‐textured soils, reduced the percentage of soil pore sizes >30 μm, but increased the proportion of medium pore sizes (≥30–50 μm), micro pore sizes (≥0.3–5 μm), and extremely micro pore sizes (<0.3 μm), owning to the clogging effect of the fine and clay particles contained in WBSM. In addition, WBSM application increased soil available water‐holding capacity and reduced evaporative water loss, which has useful implications for the management of coarse‐textured soils with a distinct water deficit in fragile ecosystems.…”
Section: Figurementioning
confidence: 99%